ANALISIS HAMBATAN BELAJAR PADA SISWA SLOW LEARNER DI KELAS IV SDN BANYUAJUH 5 BANGKALAN - Indahsari Indahsari; Jesika Yulianti; Anisa Nur Fadila; Putri Aulia Maharani; Nova Estu Harsiwi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT This study is motivated by differences in students’ learning abilities in the classroom, which cause some students, particularly slow learners, to experience difficulties in following the learning process optimally. This condition requires teachers’ attention to ensure that students’ learning needs are adequately met. The study aims to analyze the learning barriers experienced by slow learner students in Grade IV at SDN Banyuajuh 5 Bangkalan. This research employs a qualitative approach with a descriptive design. The subject of the study is the Grade IV classroom teacher, while the object of the study is the learning barriers experienced by these students. Data collection techniques were conducted through interviews and documentation. The research procedure includes data collection, data reduction, data display, and conclusion drawing. Data analysis was carried out using the Miles and Huberman model to obtain a systematic and in-depth understanding of the research conditions. The results show that slow learner students experience difficulties in reading and writing, understanding learning materials, low concentration, health-related barriers in the form of a history of epilepsy, and difficulties in following classroom instruction. These conditions cause students to require more time than their peers in understanding material and completing tasks. Teachers address these challenges through individual approaches, repetition of materials, simplified instruction, and intensive guidance. Thus, it can be concluded that the learning barriers experienced by slow learner students are academic, cognitive, and health-related in nature, requiring adaptive learning strategies. ABSTRAK Penelitian ini dilatarbelakangi oleh perbedaan kemampuan belajar siswa di kelas yang menyebabkan sebagian siswa, khususnya slow learner, mengalami hambatan dalam mengikuti pembelajaran secara optimal. Kondisi ini menuntut perhatian guru agar kebutuhan belajar siswa tetap terpenuhi. Penelitian ini bertujuan untuk menganalisis hambatan belajar siswa slow learner di kelas IV SDN Banyuajuh 5 Bangkalan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif. Subjek penelitian adalah guru kelas IV, sedangkan objek penelitian adalah hambatan belajar siswa tersebut. Teknik pengumpulan data dilakukan melalui wawancara dan dokumentasi. Tahapan penelitian meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Analisis data menggunakan model Miles dan Huberman untuk memperoleh gambaran yang sistematis dan mendalam mengenai kondisi penelitian. Hasil penelitian menunjukkan bahwa siswa slow learner mengalami hambatan membaca dan menulis, kesulitan memahami materi, rendahnya konsentrasi, hambatan kesehatan berupa riwayat epilepsi, serta kesulitan mengikuti pembelajaran di kelas. Kondisi ini membuat siswa membutuhkan waktu lebih lama dibandingkan siswa lain dalam memahami materi dan menyelesaikan tugas. Guru mengatasi hambatan tersebut melalui pendekatan individual, pengulangan materi, penyederhanaan penyampaian, serta bimbingan intensif. Dengan demikian, hambatan belajar siswa slow learner bersifat akademik, kognitif, dan kesehatan sehingga memerlukan strategi pembelajaran yang adaptif.